Criteria for measuring KM performance outcomes in organisations - Chong, Siong Choy; Wong, Kuan Yew; Lin, Binshan (Emerald Publishing Limited, 2006)
Purpose - This research attempts to comprehensively examine the criteria for measuring knowledge management (M performance outcomes in organisations. To date, no studies have provided a set of widely accepted measurement criteria associated with KM efforts. This paper, therefore, aims to fill the gap.